Dental Curriculum Revision in Iran: Dentists' Perspective on Achievement of Essential Competencies through National Curriculum. - A Fazel; A Jafari; Mr Khami; L Seddighpour; Mj Kharrazifard; M Nassibi; R Yazdani; M Soroush (Tehran University of Medical Sciences, 2013)
Based on the current emphasis on competency-based education, as a part of need assessment phase of dental curriculum revision in Iran, in the present study the dental graduates' perspective concerning the minimum competency requirements for an Iranian general dentist has been investigated.Based on the three available major competency documents in the literature a questionnaire was developed in which the participants were asked to indicate their opinion about the necessity of each of the 142 stated competencies for an Iranian general dentist (Yes/No), and to state the degree to which they believed the current curriculum covers each competency (Completely, Partially, Not at all). In an annual meeting in June 2008, the provincial chief dental managers were asked to distribute the questionnaires among general dentists in their province (10 questionnaires in each province). The managers posted back the completed questionnaires to the researchers.Of 300 questionnaires distributed in the 30 provinces of the country, 250 questionnaires (83%) were returned. While most of the participants considered the competencies as necessary for an Iranian dentist, less than 40% of the respondents believed that the graduates acquire the most required competencies of the profession during the current educational program.A necessity exists for curriculum revision. In addition to clinical skills, in this revision more emphasis also should be placed on the non-clinical part of the curriculum.